Analisis Perilaku Brand Loyalist dan Brand Switcher pada Jasa Akomodasi Bintang 5 di Kota Medan - Femmy Indriany Dalimunthe (Society, 2021)
A brand is a fundamental part of the marketing strategy in influencing purchase interest. A person’s buying ability will influence a customer to choose the product they want. In addition, higher competitiveness among hotels will create more awareness to maintain customer satisfaction and turn it into customer loyalty as the main target of their marketing. In connection with achieving customer loyalty, hotels must study the factors influencing customers to become loyal or switch from the hotel brand. A brand can be measured through brand equity which consists of a set of assets and liabilities of the Brand associated with the name and symbol of the Brand that can be given to consumers. Important and measurable components in forming brand equity include brand awareness, brand association, perceived quality, and brand loyalty. This study examines the variables that make the difference between loyalists and customers who switch hotel brands. The data used were taken from 42 respondents spread across the International Departure Terminal of Kualanamu Airport. The research method used is descriptive with a quantitative approach. The data were analyzed using the discriminant analysis method through the SPSS 12.0 program. And other limitations for this research are 5-Star Hotels and Chain International in Medan. Discriminant analysis shows that one factor requiring search variation distinguishes between brand loyalists and brand switchers. The Brand switching matrices show that all hotels serving consumers in Medan have low customer loyalty. The ratio between brand loyalists and brand switchers was 1:9, which means that only one person is loyal to one brand out of 10 consumers of accommodation services. The rest are types of consumers who like to switch to other brands.